IMPACT OF PAK-INDIA RELATIONSHIP ON RICE TRADE ON ECONOMY OF PAKISTAN BY USING COMPUTABLE GENERAL EQUILIBIUM MODEL (CGE) - Memon, Muhammad Salih; Muhammad Shaikh, Faiz; Bhatti, Dr.Nadeem; Ali Shah G.Syed, Dr.Anwar; Ram, Dr.Nanik (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2016)
This exploration researches the Impact of PAK-INDIA Rice exchange on Economy of Pakistan. Information were gathered from GTAP-7 database. Information were gathered from 60 rice exporters by utilizing straightforward irregular strategy and information were investigated by utilizing GEM-programming. Distinctive reproduction keep running on GTAP-7 database and different duty rates connected. It was uncovered that if India were evacuating the touchy rundown thing, in this situation both nations would have positive effect on GDP, Export, Import. The outcomes demonstrates that there is sure effect of Rice fare to India. It was further uncovered that if Pakistan is given MFN status to India, Pakistan's import diminished and Export expanded and general positive effect on Economy. The principal situation is when typical exchanging connection with India will be restored; it implies that both nations will give the MFN (Most Favored Nations) status to one another. In the second situation, the SAFTA will be agent and there will be unhindered commerce in the middle of India and Pakistan and both nations will uproot all levies and custom obligations from every others' imports. The Global exchange examination GTAP model is utilized to dissect the conceivable effect of SAFTA on Pakistan in a multi nation, multi segment connected General harmony casing work. Results in light of this exploration uncover that on SAFTA, grounds, here will be net fare advantages in Pakistan's economy.